ANALSISI RASIO KEUANGAN SEBELUM DAN SESUDAH SEASONED EQUITY OFFERINGS (SEO) TERHADAP PENURUNAN KINERJA PASCA PENAWARAN - Amin, M Al (Universitas Muhammadiyah Magelang, 2009)
An assesment of work performance is important to be conducted either by the management staffs, stakeholders, goverment and other stakeholders, since it is dealt with the welfare distribution among them. FASB and SFAC Number 1 states that such financial report should provide some information about the company's financial performance during a certain period of time. Financial report is useful for those house it in making some rational policies. The sample in this research includes is companies and 36 data altogether are achieved. Thoes companies are the ones conduction SEO within which the data used are the sample of the companies of financial reports ywo years before and two years after SEO. This research uses a descriptive analysis with classical assumption test on the data normality, and the satistical test is paried sample t test. The result of the research shows that there is no significant influence before and after the companies conduct SEO. This may be influenced by the economical and political changes within a country.